Cerebrospinal Fluid Analysis in Dogs and Cats with Neurological Diseases - Conceição, Renato Tavares; da Costa Flaiban, Karina Keller Marques; Guimarães, Fernanda Catacci; Bahr Arias, Mônica Vicky (Acta Scientiae Veterinariae, 2019)
Background:Cerebrospinal fluid (CSF) analysis is of great importance for evaluation of patients with central nervous system problems, because it helps to confirm or exclude many diseases when evaluated together with other relevant clinical and ancillary laboratory tests. As there are few studies in Brazil describing results of CSF analysis in dogs and cats, the objective of the present study was to evaluate results of CSF analysis in a period of ten years, grouping the changes observed, mainly total and differential cell count and total protein concentration, according to the following etiological categories of diseases: inflammatory, degenerative, traumatic, neoplastic and vascular disorders. Materials, Methods &Results:Medical records of dogs and cats with neurological diseases that had CSF collected and analyzed at a Veterinary Teaching Hospital between 2008 and 2017 were retrospectively reviewed. Patient data included breed, sex, body weight, age at presentation, findings of clinical and neurological examination, results of CSF analysis, diagnostic imaging and other laboratory tests results including PCR and serologies for infectious diseases. A total of 245 CSF exams were studied (240 dogs and five cats). The established normal range for protein concentration was less than 25 mg/dL for cisternal collection and less than 45 mg/dL for lumbar puncture. Total nucleated cell count was considered normal when less than 5 cells/µL, with a predominance of mononuclear cells. Both pleocytosis and increased concentration of the protein level were classified as discrete, moderate and marked, and the pleocytosis was further classified as mononuclear, neutrophilic and mixed cell pleocytosis. The information obtained was analyzed in relation to the neurological syndromes and etiological categories of neurological diseases. The most frequent syndrome was thoracolumbar and the less frequent was cerebellar. Regarding the etiological categories, the most frequent in decreasing order were inflammatory, infectious, degenerative, neoplastic, traumatic, vascular and episodic. CSF examination was abnormal in 72% of cases. In viral infectious diseases, there was predominantly mononuclear pleocytosis with a slight increase of protein, whereas in dogs with presumptive diagnosis of meningoencephalitis of unknown origin (MUO), marked mononuclear and mixed pleocytosis predominated with moderate to marked protein increase. In degenerative diseases, however, the absence of pleocytosis or mild pleocytosis, with normal to slightly increased protein was most observed. In neoplastic diseases there was a high frequency of mild to moderate pleocytosis, with and without albuminocytological dissociation, while in spinal trauma there was mainly mononuclear pleocytosis. A slight increase in protein was observed mainly in infectious, degenerative, neoplastic and traumatic diseases, while moderate to marked increase was more observed in cases of presumptive diagnosis of MUO. Albuminocytological dissociation was observed in half of the cases of neoplasia and less frequently in degenerative, infectious and traumatic diseases. Discussion: The exam was altered in a considerable number of patientsand provided important information even when normal. The diseases with more abnormalities were inflammatory/infectious and neoplastic diseases. When the exam was normal, the most frequent condition was degenerative diseases. Although the changes were not specific for each class of neurological disease, there were certain trends regarding pleocytosis type and protein increase in some of them. Based on the results of this retrospective study, result of CSF analysis, when interpreted along with signalment, etiological categories of diseases, neurological syndromes, and results of other complementary tests, provided support for the diagnosis of various neurological diseases.